2013
DOI: 10.1179/1607845412y.0000000070
|View full text |Cite
|
Sign up to set email alerts
|

Increased VWF antigen levels and decreased ADAMTS13 activity in preeclampsia

Abstract: This study aimed to assess the von Willebrand factor (VWF) antigen levels and its proteolytic enzyme ADAMTS13 activity in preeclampsia. The study includes 10 non-pregnant women, 50 normal pregnancy, and 110 preeclamptic (PE) women at the same period of pregnancy. For all studied groups plasma ADAMTS13 activities were determined with the FRETs-VWF 73 assay, while VWF antigen levels with an immunoturbometric assay. The plasma ADAMTS13 activity was significantly reduced in PE as compared with normal pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 15 publications
1
40
1
2
Order By: Relevance
“…Inhibitors of VEGF function such as sFlt-1 are known to cause endothelial activation 42 and release of VWF. 11,43 In the ADAMTS13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibitors of VEGF function such as sFlt-1 are known to cause endothelial activation 42 and release of VWF. 11,43 In the ADAMTS13…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Likewise, small studies have reported a decrease in ADAMTS13 activities in patients with severe preeclampsia, with ADAMTS13 activity #70% being associated with early-onset preeclampsia, independent of VWF-Ag levels. 11,54 However, it is not known if these alterations antedate clinical symptoms. Future studies should evaluate whether low ADAMTS13 activity is a determinant of HELLP syndrome among patients with preeclampsia who have high sFlt-1 levels.…”
Section: /2mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although sFLT-1 is almost certainly one of the key factors driving preeclampsia, there are also reports that ADAMTS13 activity is commonly reduced in patients with preeclampsia. 8,9 ADAMTS13 is a protease that cleaves large vWf multimers that are released from activated endothelial cells, thereby blocking local platelet aggregation and thrombosis. Erpenbeck et al 6 show that overexpression of sFLT-1 in control mice induced mild manifestations of TMAs, which has been previously reported, whereas a lack of ADAMTS13 resulted in no manifestations of TMAs.…”
mentioning
confidence: 99%
“…ADAMTS13 activity often falls below threshold level in antiphospholipid syndrome [27]. Besides, the connection between the decrease of ADAMTS-13 activity and the increase of RCoA and vWF antigen in pregnant women with pre-eclampsia has recently been shown [28]. In general, it can be assumed that the increase of RCoA and vWF level is not that significant for pregnancy as the decrease of ADAMTS-13 activity and antigen potentially contributing to the increase of this factor multimerization and increase of platelet activation reaching delivery.…”
Section: Partmentioning
confidence: 99%